ANALYSIS OF THE PARAMETERS OF SMART MEASURING DEVICES IN PHOTOVOLTAIC SYSTEMS: ANALYSIS OF THE PARAMETERS OF SMART MEASURING DEVICES IN PHOTOVOLTAIC SYSTEMS - Ivanova, Iliyana (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
The development of photovoltaic (PV) systems and the need for efficient energy flow management have established smart measuring devices (smart meters and loggers) as key components. They provide bidirectional measurement of energy production and consumption, remote monitoring capabilities and integration with inverters, controllers and cloud platforms. This paper presents a classification of the different device types. Their technical characteristics, communication technologies, accuracy, self-consumption and range of applications are analyzed. The analysis facilitates the selection of suitable solutions tailored to specific needs, ranging from household to industrial applications.